166k views
3 votes
Solve for x.

z = 6 π x y



A. z
---
6 π y= x

B. x = 6 π y z

C. z
---
6 π = x

D. z
---
6 = x


If you can, Please explain your answer!

Solve for x. z = 6 π x y A. z --- 6 π y= x B. x = 6 π y z C. z --- 6 π = x D. z --- 6 = x-example-1
User Batajus
by
5.9k points

2 Answers

5 votes

Answer:

a

Explanation:

Solve for x. z = 6 π x y A. z --- 6 π y= x B. x = 6 π y z C. z --- 6 π = x D. z --- 6 = x-example-1
User Dialogik
by
5.8k points
6 votes
The answer to the question is a
Solve for x. z = 6 π x y A. z --- 6 π y= x B. x = 6 π y z C. z --- 6 π = x D. z --- 6 = x-example-1
User Mendelt
by
5.7k points